Postal Consumer Protection: Comparison of Indonesian Law with Malaysia and Vietnam - Fadli Zaini Dalimunthe (Buletin Pos dan Telekomunikasi, 2021)
Post is one type of communication media used by the public to send goods from one place to another. The public as consumers needs protection in using postal services, especially related to after-sales services. This paper discusses and analyzes postal consumer protection regulations in Indonesia, Malaysia, and Vietnam. This paper uses legal research methods normative with the Statute Approach and the Comparative Approach. The results show consumer protection is the responsibility of the postal operator for the services provided. Each country has regulations related to the protection of postal consumers. It regulates events that can cause loss to consumers and can be requested for compensation from postal providers, such as loss, misdelivery, delay, or damage. There are slightly different regulations and specific each country. Malaysia has a special agency for consumer dispute resolution in the communication and multimedia sector, one of which is related to the postal sector. Vietnam regulates the time limit for consumer complaints and dispute resolution.